OPPORTUNITIES AND CHALLENGES FOR THE LOCALIZATION OF SDG 6: AN EXPERIENCE IN THE SÃO PAULO METROPOLITAN REGION - Mancini, Rodrigo [UNESP]; Paulino, Sonia (Fundacao de Apoio a Pesquisa, Tecnologia e Inovacao, 2024)
The localization of the Sustainable Development Goals (SDGs) within municipalities has emerged as an opportunity for the evolution of multi-level governance processes. In this article, the objective was to analyze a practical experience of environmental policy decentralization in the “bottom-up” localization of SDG 6, through the water management actions of the Programa Municipal Verde Azul (Green-Blue Municipality Program, GBMP). Four municipalities were selected from the São Paulo Metropolitan Region that are located within areas of springs or water sources of extreme importance for the water supply of the local population therein. As the method, participatory action-research was adopted with consultation of municipal reports and plans for situational analysis, in addition to workshops and interviews being undertaken. The principal findings showed that the SDG localization process, analyzed with the support of the SDG Synergies tool, allowed public managers clearly to visualize other SDGs that might be impacted by the GBMP’s actions, as well as by the intensity of these interactions and the importance placed on multi-level governance. Conversely, despite the region boasting a significant institutional arrangement, there was a notable lack of synergy amongst the main bodies involved, with difficulties in structuring a more effective and efficient model of multi-level governance persisting. In this context, the SDGs are at risk of becoming merely another filler field in municipal and regional plans and programs, rather than inspiring effective and necessary policy changes.
OPORTUNIDADES E DESAFIOS PARA A LOCALIZAÇÃO DO ODS 6: UMA EXPERIÊNCIA NA REGIÃO METROPOLITANA DE SÃO PAULO
Keywords: 2030 Agenda; Multi-level Governance; Municipalities; Sustainable Regional Development